Aircraft selection with DEA's triple index: an approach for sustainability - Mariano, Enzo Barberio [UNESP]; Reinas, Rafael Iglesias; Sobreiro, Vinicius Amorim; Rebelatto, Daisy Aparecida do Nascimento (Inderscience Publishers, 2014)
The objective of this paper is to present a benefit-cost ranking of 127 civil transport aircraft; this ranking was determined considering a new data envelopment analysis (DEA) approach, called triple index, which combines three assessment methods: 1) standard frontier, 2) inverted index; 3) cross-multiplicative index. The analysis used the following inputs: a) market price; b) direct operating costs; and as outputs: a) payload, b) cruise speed; c) maximum rate of climb with a single engine. To ensure the homogeneity of the units, the aircrafts were divided according to the propulsion system (jet and turboprop) and size (regional, narrow-body and wide-body); they were also evaluated according to different ranges in order to identify the aircraft with the best cost-benefit relationship for each option.
Keywords: Data envelopment analysis; DEA; Cost-benefit analysis; Aircraft; Triple index; Sustainability